The TIME concept evolution in British discourse - Вondarenko, Ye. V. (Cognition, Communication, Discourse, 2018)
The article reviews basic tendencies of evolution of the TIME concept in mythical and scientific (philosophical) types of discourse in Great Britain of 10th c. BC – 21st c. AD. The concept is modelled as a conceptual network, which allows singling out propositional relations of the TIME concept with other concepts. The research features the considered concept in British philosophical discourse of the 21st c. as an evolutionary product of the time models of the previous epochs.